Dagger From Bolshie Tarkhany With Crossguard Details In The Form Of A Relief “Comma” - Chizhevsky Andrei A.; Gismatullin Marat R.; Khramchenkova Rezida Kh. (Археология евразийских степей, 2022)
A bronze dagger and arrowhead discovered in the vicinity of Bolshie Tarkhany village of the Republic of Tatarstan are rare types of weapons for the territory of the Ananyino Cultural and Historical Region. No direct counterparts to the dagger are known, however, items with details or ornamentation elements in the form of a comma are available in the collections of the Aldy-Bel, Early Saka and Tasmola cultures. The arrowhead with an elongated asymmetric rhomboid feather and a slightly protruding bushing, accompanying the dagger, belongs to the so-called Yenzhe type, which is mainly widespread in the steppe and forest-steppe areas of Eurasia. Overlapping of the chronological intervals of the dagger and arrowhead makes it possible to date the complex from Bolshie Tarkhany within the framework of stage I-2 of the Early Ananyino Cultural and Historical Region period (mid-8th – first half of the 7th century BC). According to spectral analysis results, the dagger was made of a rare group of tin-arsenic bronze metal with a high content of silver, bismuth and nickel. Four items from Relka and Starshiy Akhmylovsky burial grounds, as well as from Munovsky II settlement, are its close counterparts in terms of the elemental ratio. The tin-arsenic bronze group with a nickel admixture from the early Tagar period of Khakassia has a similar macro-composition of the metal.